2011
DOI: 10.1111/j.1365-2885.2010.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Silybin inhibits interleukin‐1β‐induced production of pro‐inflammatory mediators in canine hepatocyte cultures

Abstract: Hepatocytes are highly susceptible to cytokine stimulation and are fundamental to liver function. We established primary canine hepatocyte cultures to study effects of anti-inflammatory agents with hepatoprotective properties. Hepatocyte cultures were incubated with control media alone, silybin (SB), or the more bioavailable silybin-phosphatidylcholine complex (SPC), followed by activation with interleukin-1 beta (IL-1β; 10 ng/mL). Inflammatory response was measured by prostaglandin E2 (PGE(2) ), interleukin-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 72 publications
(154 reference statements)
2
30
0
Order By: Relevance
“…The chemokine CCL2 is secreted by Kupffer cells, injured hepatocytes, and activated hepatic stellate cells, and leads to monocyte recruitment, macrophage activation, progressive inflammation, and fibrogenesis during liver injury . It has not been studied previously in dogs with liver disease, but CCL2 production by canine hepatocytes was inhibited in vitro by the commercially available liver protectant, silybin . Increased serum CCL2 concentrations also have been found in critically ill dogs, and in those with lymphoma, histiocytic sarcoma, pulmonary fibrosis, congestive heart failure, and immune‐mediated hemolytic anemia .…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine CCL2 is secreted by Kupffer cells, injured hepatocytes, and activated hepatic stellate cells, and leads to monocyte recruitment, macrophage activation, progressive inflammation, and fibrogenesis during liver injury . It has not been studied previously in dogs with liver disease, but CCL2 production by canine hepatocytes was inhibited in vitro by the commercially available liver protectant, silybin . Increased serum CCL2 concentrations also have been found in critically ill dogs, and in those with lymphoma, histiocytic sarcoma, pulmonary fibrosis, congestive heart failure, and immune‐mediated hemolytic anemia .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that silibinin is exerting its anti-inflammatory actions by inhibiting the activity of NF-κB. Indeed, in non-gestational tissues, silibinin has been shown to exert its effects by inhibiting the activity of NF-κB [27], [40], [55].…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin has been utilised as an effective treatment for hepatic disease [23] and as an adjunctive cancer therapy [24], [25]. Silibinin has been shown to have potent anti-inflammatory and anti-cancer effects (reviewed in [26]); silibinin reduced pro-inflammatory mediators in vitro in canine hepatocytes [27], an HIV viral infection model [28], in vitro and in vivo models of mouse skin inflammation [29], [30], and skin and prostate cancer cells from animal models [24]. In mouse models of allergic inflammation [31] and infection-induced sepsis [32], silibinin decreased inflammation and increased survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary to lipopolysaccharide (LPS) stimulation, silibinin inhibits inducible nitric‐oxide synthase expression in vitro . Multiple in vitro studies in stellate cells and hepatocytes have demonstrated a reduction in monocyte chemoattractant protein 1 secondary to interleukin (IL) 1β stimulation . IL‐1β and prostaglandin E2 have been decreased in vivo with silibinin administration, which also improved survival in a mouse LPS sepsis model .…”
Section: Pharmacodynamicsmentioning
confidence: 99%